AI-Enhanced Sustainable Infrastructure Planning for Mega Pilgrimages - Ahmed Mohamed Sayed Ahmed (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Mega pilgrimages, such as the Hajj in Saudi Arabia, represent one of the most complex urban and infrastructural planning challenges in the modern world. These events bring millions of participants into condensed urban spaces, testing the limits of transportation systems, healthcare services, environmental sustainability, and public safety. Traditional infrastructure planning methods often fall short in responding dynamically to such scale and unpredictability. This paper explores how Artificial Intelligence (AI) can be leveraged to transform infrastructure planning for mega pilgrimages into a more sustainable, adaptive, and resilient process. Through a systematic literature review and the integration of cross-disciplinary insights, we propose a conceptual AI-enhanced infrastructure framework that addresses real-time urban mobility, environmental resilience, and healthcare delivery during mass gatherings. Focusing particularly on the context of Saudi Arabia and its Vision 2030 initiatives, this study demonstrates the capacity of AI technologies ranging from predictive analytics to autonomous systems to strengthen critical infrastructure, reduce environmental impact, and improve crowd management. Our findings advocate for the integration of AI-driven approaches into national planning agendas for mega events, emphasizing the need for ethical governance, data infrastructure, and inter-agency coordination.